The UN Decade of healthy ageing: strengthening measurement for monitoring health and wellbeing of older people. (1st July 2022) - Amuthavalli Thiyagarajan, Jotheeswaran; Mikton, Christopher; Harwood, Rowan H; Gichu, Muthoni; Gaigbe-Togbe, Victor; Jhamba, Tapiwa; Pokorna, Daniela; Stoevska, Valentina; Hada, Rio; Steffan, Grace Sanico; Liena, Ana; Rocard, Eileen; et al.
Abstract: Over the past 100 years, life expectancy has increased dramatically in nearly all nations. Yet, these extra years of life gained have not all been healthy, particularly for older people aged 60 years and over. In 2020, the World Health Organisation (WHO) and United Nations (UN) member states embraced a sweeping 10-year global plan of action to ensure all older people can live long and healthy lives, formally known as the UN Decade of Healthy Ageing (2021–2030). With the adoption of the UN Decade of Healthy Ageing resolution, countries are committed to implementing collaborative actions to improve the lives of older people, their families and the communities in which they reside. The Decade addresses four interconnected areas of action. Adopting the UN's resolution on the Decade of Healthy Ageing has caused excitement, but a question that has weighed on everyone's mind is how governments will be held accountable? Besides, there have been no goals or targets set for the UN Decade of Healthy Ageing from a programmatic perspective for the action areas, and guidance on measures, data collection, analysis and reporting are urgently needed to support global, regional and national monitoring of the national strategies, programmes and policies. To this end, WHO in collaboration with UN agencies and international agencies established a Technical Advisory Group for Measurement of Healthy Ageing (TAG4MHA) to provide advice on the measurement, monitoring and evaluation of the UN Decade of Healthy Ageing at the global, regional and national levels.